The Kaleidoscopic Study of Chinua Achebe’s No Longer at Ease. (International Journal of Food and Nutritional Sciences, 2022)
Chinua Achebe is a reputed African novelist who has facilitated the world to understand the colonial and the post colonial condition of Africa especially Nigeria by focusing his attention on the African customs, traditions, rituals and practices. His works mainly focus on the socio-political conditions, exposing the corrupt practices and the African’s desire for western lifestyle. The novel No Longer at Ease is a powerful novel that truthfully depicts the impact of colonialism on the African society which has caused both positive and negative effects. The degradation of cultural and ethical values has ruined the African social system. The indigenous people are attracted by the fashionable and comfortable life of the colonizers. Earlier, African tribes had no proper educational system and structure and hence, they were not exposed to the scientific advancements and the benefits of science and education but later the colonizers provided them with education and in the present day the African community has occupied respectable position in the world arena.